Radial Distribution Function Analysis of the Polyamide Thin Film Composite formation using Trimesoyl Chloride and Piperazine - Wan Zulaisa Amira, Wan Jusoh; Sunarti, Abd Rahman; A. L., Ahmad; N. M., Mohktar (Penerbit UMP, 2019)
Polyamide thin film composite (TFC) membranes are well known for their performance and strength which normally applied in pervaporation dehydration and reverse osmosis field. TFC is produced by the rapid reaction between aqueous and organic monomer. However, the interaction between monomers is not well discussed at the atomic level and there is no precise tool to measure the effectiveness of the selection of organic with the aqueous monomer to form a stable TFC layer. Thus, this paper aims to analyze the interaction between aqueous monomer and organic monomer using the Molecular Dynamic (MD) simulation to form the TFC membrane. This work was done by using Piperazine (PIP) as the aqueous monomer with the combination of Trimesoyl Chloride (TMC) as the organic monomer in the binary systems. The simulation involved the setting of Ewald Summation Method, COMPASS force field, equilibrium phase by microcanonical, NVE (constant volumes and total energy) and run-production stage by NPT (constant pressure and temperature). Analysis by the Radial distribution function (RDF) explicates the intermolecular interfacial of 5.75 Å between the bonding of N (Amine) - C (TMC) atoms at the distance of 1.0 Å. This study suggested that the TFC formed by the interaction between TMC - PIP is very much stable based on the higher interaction in a very short distance.